A Review on Bat Algorithm - Yadav, SL; Phogat, M (International Journal of Computer Sciences and Engineering, 2025)
Complications of cracking real world glitches with their promising difficulties forced computer technologist to search for more skillful problem solving approaches. Meta-heuristic procedures are outstanding models of these methods and out of these the bat algorithm (BA) is a good example. BAT algorithm is found very efficient in solving difficult problems. This algorithm has been advanced hurriedly and has been practical in different optimization jobs. The literature has extended substantially since last seven years. This paper offers appropriate study of the various modifications of BAT algorithm.